MORC4, a novel member of the MORC family, is highly expressed in a subset of diffuse large B‐cell lymphomas - Liggins, Amanda P.; Cooper, Christopher D. O.; Lawrie, Charles H.; Brown, Philip J.; Collins, Graham P.; Hatton, Chris S.; Pulford, Karen; Banham, Alison H. (British journal of haematology, 2007)
Summary The OX‐TES‐4 antigen originally elicited an antibody response in 50% of diffuse large B‐cell lymphoma (DLBCL) patients but not in control subjects. OX‐TES‐4 is encoded by a novel gene, MORC4, located at chromosome Xq22.3. The MORC4 protein contains a HATPase‐c domain, CW zinc finger motif, nuclear localisation signals and a nuclear matrix‐binding domain, together with a coiled‐coil region. MORC4 mRNA is widely expressed at low levels in normal tissues, showing highest expression levels in placenta and testis. mRNA levels were increased in non‐germinal centre‐derived DLBCL and Hodgkin lymphoma cell lines, compared with germinal centre‐derived DLBCL cell lines and normal B cells. Nineteen DLBCL patients (66%) expressed significantly higher levels of MORC4 mRNA than normal B cells (P = 0·0031). The differential expression of MORC4 identifies this molecule as a potential lymphoma biomarker, whose overexpression may contribute to the immunological recognition of MORC4 by a subgroup of DLBCL patients.